Screening method of quaternary spinel ferrite type photocatalytic material
By constructing a quaternary spinel ferrite model and performing calculations and screening, the problems of resource waste and long cycle in existing technologies have been solved, enabling rapid and accurate screening and cost-reducing design of photocatalytic materials, thus promoting the development of new materials.
Patent Information
- Application Number
- CN202511574341.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-27
AI Technical Summary
The design and development of existing quaternary spinel ferrite photocatalytic materials rely on experimental exploration, resulting in resource waste, long development cycles, high costs, and difficulty in rapid promotion and application.
By constructing a quaternary spinel ferrite model, and using first-principles calculations for structural relaxation, phonon spectrum calculations, formation energy calculations, and static self-consistent calculations, suitable materials for photocatalysis are screened out, avoiding the use of experimental equipment and reagents.
This enables the rapid and accurate screening of suitable photocatalytic materials, reducing costs, shortening design cycles, and promoting the rapid development of materials.
Smart Images

Figure CN121415951A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of design and development of multi-component semiconductor photocatalytic materials, and particularly to a screening method for quaternary spinel ferrite photocatalytic materials, belonging to the field of new energy materials technology. Background Technology
[0002] Committed to achieving sustainable energy development, semiconductor photocatalysis technology has garnered significant attention since its emergence over fifty years ago. However, existing photocatalytic materials suffer from problems such as poor visible light absorption, non-spontaneous reaction processes, and low quantum conversion efficiency in the visible light region, making the demand for efficient and low-cost semiconductor photocatalytic materials increasingly urgent. Novel, efficient, and stable semiconductor photocatalytic materials remain a hot research topic in the field of photocatalysis.
[0003] Spinel ferrites are composed of two basic structural units: FeO6 octahedral ionic groups and tetrahedral central cations. Previous studies have shown that the bandgap of spinel ferrites with alkali metals or alkaline earth metals at the A-site is mainly determined by the FeO6 octahedral ionic groups, and is approximately 2.0 eV, meeting the bandgap requirements for photocatalytic water splitting and exhibiting good visible light absorption. Secondly, literature reports that the spinel lattice maintains good stability even when the elemental ratio of the tetrahedral central cation changes. Thirdly, spinel ferrites are abundant in the Earth's crust. These characteristics make spinel ferrites a naturally inexpensive and highly efficient candidate material for photocatalysis.
[0004] Currently, research on the application of quaternary spinel ferrites in photocatalysis is still in its early stages, with most existing explorations focused on the experimental field. The design of new materials in the experimental field is often based on a trial-and-error research approach, requiring significant investment of human and material resources. Furthermore, this research and development model leads to a long overall cycle from material design to development, resulting in high economic costs. This, to some extent, restricts the promotion and application of quaternary spinel ferrite materials in photocatalysis.
[0005] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a method for screening quaternary spinel ferrite photocatalytic materials. The method is characterized by its speed and accuracy, and it provides direct theoretical guidance for the design and development of novel quaternary spinel ferrite photocatalytic materials. This method does not rely on large-scale experimental equipment, consumes no experimental consumables, or use any experimental reagents; it is safe and pollution-free, and can significantly reduce the cost of material design. Furthermore, this method can shorten the material design cycle and promote the rapid development of novel quaternary spinel ferrite photocatalytic materials. Summary of the Invention
[0006] To address the aforementioned problems, the present invention aims to provide a method for screening quaternary spinel ferrite photocatalytic materials.
[0007] To achieve the above objectives, the technical solution adopted in this invention involves constructing a series of quaternary spinel ferrite models, followed by thorough structural relaxation using first-principles calculations. The thermodynamic and kinetic stability is evaluated through formation energy and phonon spectrum calculations. Furthermore, the band structure, band edge positions, effective electron mass, and effective hole mass are calculated. The influence of different tetrahedral central atoms on the electronic structure of the spinel material is analyzed and compared. Based on the requirements of ideal photocatalytic materials for electronic structure, effective electron mass, and effective hole mass, suitable quaternary spinel materials for photocatalysis are selected. The implementation method includes the following steps: (1) Model building a. Construct a spinel-type Fe3O4 geometric structure model, perform sufficient structural relaxation on it, and obtain the ground-state Fe3O4 geometric structure model; b. Replace all Fe atoms in the tetrahedral center of the ground state Fe3O4 geometric structure model obtained in step (1) a with divalent metal atoms A to obtain the ternary spinel ferrite AFe2O4 geometric structure model. Perform sufficient structural relaxation on it to obtain the ground state AFe2O4 geometric structure model. c. By partially replacing metal atom A in the ground-state AFe2O4 geometric structure model obtained in step (1) b with divalent metal atom B, a quasi-random structure A of quaternary spinel ferrite with different proportions of tetrahedral central elements is constructed. x B y Fe2O4( x + y = 1), and perform sufficient structural relaxation on it to obtain the ground state quaternary A at each scale. x B y Geometric structure model of Fe2O4; (2) Property calculation a. Phonon spectrum calculation The ground-state quaternary spinel A obtained in step (1)c x B y The Fe2O4 geometric structure model was used to perform cell expansion operations, set the corresponding parameters, calculate its phonon spectrum, select the dynamically stable structural model for subsequent calculations, and eliminate unstable models. b. Formation energy calculation Calculate the formation energy of the selected structural model in step (2) a, and select the structural model with a formation energy less than 0 for subsequent calculations; c. Static self-consistent calculation For the structural models selected in step (2)b, perform static self-consistent calculations to generate wave function and charge density data files for each system and obtain ground state energy; d. Calculation of electronic properties Based on the charge density and wave function files obtained in step (2)c, modify the input file parameters and calculate the band structure, band edge position, effective electron mass, and effective hole mass in sequence. (3) Results processing and analysis a. Based on the calculation results of step 2(d), draw the band structure diagram and extract the band gap width; b. Based on the calculation results of step 2(d), draw a diagram showing the relationship between the edge position and the proportion of the tetrahedron's central element; c. Based on the calculation results of step 2(d), calculate the ratio of the effective electron mass to the effective hole mass; d. Based on the results of step (3)ad, analyze and compare the effects of different tetrahedral central atoms on the electronic structure, effective electron mass, and effective hole mass of spinel materials. Based on the requirements of ideal photocatalytic materials for the electronic structure, effective electron mass, and effective hole mass of materials, screen out quaternary spinel materials suitable for photocatalysis.
[0008] Preferably, the spinel-type Fe3O4 geometric structure model constructed in step 1(a) is a single cell containing 56 atoms.
[0009] Preferably, the divalent metal atom A and divalent metal atom B mentioned in step (1)b and step 1(c) are different kinds of divalent metal atoms, namely one of Mg, Ca, Sr, Ba, Zn, Cd, Fe, Co, Ni, Cu and Mn atoms.
[0010] Preferably, in step (1)c, the mcsqs module of ATAT software is used to obtain the quasi-random structure of the quaternary spinel. Structural relaxation is performed on each generated quasi-random structure, and the structure with the lowest energy is preferred as the ground-state quaternary A. x B y Geometric structure model of Fe2O4.
[0011] Preferably, the percentage of the central element A in the quasi-random structure of the quaternary spinel tetrahedron constructed in step (1) varies within the range of 12.5 at.%, 25 at.%, 37.5 at.%, 50 at.%, 62.5 at.%, 75 at.%, and 87.5 at.%.
[0012] Preferably, the sum of the percentage of the central element A and the percentage of the central element B of the quasi-random structured quaternary spinel tetrahedron constructed in step (1) is 1.
[0013] Preferably, in step (2)a, only the phonon spectrum with no imaginary frequency or an imaginary frequency less than 20 cm⁻¹ is retained. -1 *i's structural model, eliminating phonon spectra with imaginary frequencies greater than 20 cm⁻¹. -1 *i structural model.
[0014] Preferably, the screening condition for the effective electron mass and effective hole mass in step (3)e is that the ratio of the effective hole mass to the effective electron mass is greater than 10. Attached Figure Description
[0015] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.
[0016] Figure 1 It is a flowchart of the technical route for the specific research; Figure 2 It is Mg 0.125 Cd 0.875 Schematic diagram of the structure of Fe2O4 spinel; Figure 3 It is spinel-type Mg 0.125 Cd 0.875 Band structure diagram of Fe2O4. Detailed Implementation
[0017] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] To make the objectives and technical solutions of this invention clearer, the following discussion uses quaternary spinel-type ferrite A as an example. x B y Using Fe2O4 (A = Mg, B = Cd) as an example, to further understand the technical solution and advantages of the present invention, the specific calculation process is as follows: Figure 1 As shown. Example 1
[0019] (1) Model building a. Construct a spinel-type Fe3O4 geometric structure model containing 56 atoms, and perform sufficient structural relaxation on it to obtain the ground-state Fe3O4 geometric structure model; b. Replace all Fe atoms in the tetrahedral center of the ground state Fe3O4 geometric structure model obtained in step (1) a with divalent metal atoms Mg to obtain the ternary spinel ferrite MgFe2O4 geometric structure model. Perform sufficient structural relaxation on it to obtain the ground state MgFe2O4 geometric structure model. c. By partially replacing the Mg atoms in the ground-state MgFe2O4 geometric model obtained in step (1)b with divalent metal atoms Cd, quaternary spinel-type ferrites with different tetrahedral central element ratios are constructed using the mcsqs module of ATAT software. 0.125 Cd 0.875 Fe2O4, Mg 0.25 Cd 0.75 Fe2O4, Mg 0.375 Cd 0.625 Fe2O4, Mg 0.5 Cd 0.5 Fe2O4, Mg 0.625 Cd 0.375 Fe2O4, Mg 0.75 Cd 0.25 Fe2O4, Mg 0.875 Cd 0.125 The quasi-random structure of Fe2O4 was obtained by performing structural relaxation on each generated quasi-random structure, and the structure with the lowest energy was selected as the ground-state quaternary Mg. 0.125 Cd 0.875 Fe2O4, Mg 0.25 Cd 0.75 Fe2O4, Mg 0.375 Cd 0.625 Fe2O4, Mg 0.5 Cd 0.5 Fe2O4, Mg 0.625 Cd 0.375 Fe2O4, Mg 0.75 Cd 0.25 Fe2O4, Mg 0.875 Cd 0.125 Fe2O4 geometric structure model Figure 2 With Mg 0.125 Cd 0.875 Taking Fe2O4 as an example, the structural characteristics of this type of spinel model are illustrated; (2) Property calculation a. Phonon spectrum calculation The ground-state quaternary spinel Mg obtained in step (1)c 0.125 Cd 0.875 Fe2O4, Mg0.25 Cd 0.75 Fe2O4, Mg 0.375 Cd 0.625 Fe2O4, Mg 0.5 Cd 0.5 Fe2O4, Mg 0.625 Cd 0.375 Fe2O4, Mg 0.75 Cd 0.25 Fe2O4, Mg 0.875 Cd 0.125 A geometric model of Fe2O4 was used to construct a 2x2 supercell structure through cell expansion. Appropriate parameters were set, and its phonon spectrum was calculated, retaining phonon spectra with no imaginary frequencies or imaginary frequencies less than 20 cm⁻¹. -1 *i's structural model, eliminating phonon spectra with imaginary frequencies greater than 20 cm⁻¹. -1 *i's structural model; b. Formation energy calculation The formation energy of the selected structural model in step (2)a was calculated, and the results showed that Mg 0.125 Cd 0.875 Fe2O4, Mg 0.25 Cd 0.75 Fe2O4, Mg 0.375 Cd 0.625 Fe2O4, Mg 0.5 Cd 0.5 Fe2O4, Mg 0.625 Cd 0.375 Fe2O4, Mg 0.75 Cd 0.25 Fe2O4, Mg 0.875 Cd 0.125 The formation energy of Fe2O4 is less than 0, which means it is thermodynamically stable. Therefore, structural models with a formation energy of less than 0 are preferred for subsequent calculations. c. Static self-consistent calculation For the structural models selected in step (2)b, perform static self-consistent calculations to generate wave function and charge density data files for each system and obtain ground state energy; d. Calculation of electronic properties Based on the charge density and wave function file obtained in step (2)c, modify the input file parameters and calculate the band structure, band edge position, effective electron mass, and effective hole mass in sequence. (3) Results processing and analysis a. Based on the calculation results of step 2(d), draw the band structure diagram and extract the band gap width. Figure 3 It is spinel-type Mg 0.125 Cd 0.875 Band structure diagram of Fe2O4; b. Based on the calculation results of step 2(d), draw a diagram showing the relationship between the edge position and the proportion of the tetrahedron's central element; c. Based on the calculation results of step 2(d), calculate the ratio of the effective electron mass to the effective hole mass; d. Based on the results of step (3)ad, analyze and compare the effects of different tetrahedral central atoms on the electronic structure, effective electron mass, and effective hole mass of spinel-type materials. According to the requirements of ideal photocatalytic materials on the electronic structure, effective electron mass, and effective hole mass, Mg with a ratio of effective hole mass to effective electron mass greater than 10 is eliminated. 0.75 Cd 0.25 Fe2O4, Mg 0.875 Cd 0.125 Fe2O4, screening for quaternary spinel-type Mg suitable for photocatalysis. 0.125 Cd 0.875 Fe2O4, Mg 0.25 Cd 0.75 Fe2O4, Mg 0.375 Cd 0.625 Fe2O4, Mg 0.5 Cd 0.5 Fe2O4, Mg 0.625 Cd 0.375 Fe2O4. Example 2
[0020] (1) Model building a. Construct a spinel-type Fe3O4 geometric structure model containing 56 atoms, and perform sufficient structural relaxation on it to obtain the ground-state Fe3O4 geometric structure model; b. Replace all Fe atoms in the tetrahedral center of the ground state Fe3O4 geometric structure model obtained in step (1) a with divalent metal atoms Sr to obtain the ternary spinel ferrite SrFe2O4 geometric structure model. Perform sufficient structural relaxation on it to obtain the ground state SrFe2O4 geometric structure model. c. By partially replacing the Sr atoms in the ground-state SrFe2O4 geometric model obtained in step (1)b with divalent metal atoms Co, quaternary spinel-type ferrites Co with different tetrahedral central element ratios are constructed using the mcsqs module of ATAT software. 0.125 Sr 0.875 Fe2O4, Co 0.25 Sr 0.75 Fe2O4, Co 0.375 Sr 0.625 Fe2O4, Co 0.5 Sr 0.5 Fe2O4, Co 0.625 Sr 0.375Fe2O4, Co 0.75 Sr 0.25 Fe2O4, Co 0.875 Sr 0.125 The quasi-random structure of Fe2O4 was obtained by structural relaxation of each generated quasi-random structure, and the structure with the lowest energy was selected as the ground-state quaternary Co. 0.125 Sr 0.875 Fe2O4, Co 0.25 Sr 0.75 Fe2O4, Co 0.375 Sr 0.625 Fe2O4, Co 0.5 Sr 0.5 Fe2O4, Co 0.625 Sr 0.375 Fe2O4, Co 0.75 Sr 0.25 Fe2O4, Co 0.875 Sr 0.125 Geometric structure model of Fe2O4; (2) Property calculation a. Phonon spectrum calculation The ground-state quaternary spinel Co obtained in step (1)c 0.125 Sr 0.875 Fe2O4, Co 0.25 Sr 0.75 Fe2O4, Co 0.375 Sr 0.625 Fe2O4, Co 0.5 Sr 0.5 Fe2O4, Co 0.625 Sr 0.375 Fe2O4, Co 0.75 Sr 0.25 Fe2O4, Co 0.875 Sr 0.125 A geometric model of Fe2O4 was used to construct a 2x2 supercell structure through cell expansion. Appropriate parameters were set, and its phonon spectrum was calculated, retaining phonon spectra with no imaginary frequencies or imaginary frequencies less than 20 cm⁻¹. -1 *i's structural model, eliminating phonon spectra with imaginary frequencies greater than 20 cm⁻¹. -1 *i's structural model; b. Formation energy calculation The formation energy of the selected structural model in step (2)a is calculated, and the results show that Co 0.125 Sr 0.875 Fe2O4, Co 0.25 Sr 0.75 Fe2O4, Co 0.375 Sr 0.625 Fe2O4, Co 0.5 Sr0.5 Fe2O4, Co 0.625 Sr 0.375 Fe2O4, Co 0.75 Sr 0.25 Fe2O4, Co 0.875 Sr 0.125 The formation energy of Fe2O4 is less than 0, which means it is thermodynamically stable. Therefore, structural models with a formation energy of less than 0 are preferred for subsequent calculations. c. Static self-consistent calculation For the structural models selected in step (2)b, perform static self-consistent calculations to generate wave function and charge density data files for each system and obtain ground state energy; d. Calculation of electronic properties Based on the charge density and wave function files obtained in step (2)c, modify the input file parameters and calculate the band structure, band edge position, effective electron mass, and effective hole mass in sequence. (3) Results processing and analysis a. Based on the calculation results of step 2(d), draw the band structure diagram and extract the band gap width; b. Based on the calculation results of step 2(d), draw a diagram showing the relationship between the edge position and the proportion of the tetrahedron's central element; c. Based on the calculation results of step 2(d), calculate the ratio of the effective electron mass to the effective hole mass; d. Based on the results of step (3)ad, analyze and compare the influence of different tetrahedral central atoms on the electronic structure, effective electron mass, and effective hole mass of spinel-type materials. According to the requirements of ideal photocatalytic materials on the electronic structure, effective electron mass, and effective hole mass, eliminate Co materials with a ratio of effective hole mass to effective electron mass greater than 10. 0.75 Sr 0.25 Fe2O4, Co 0.875 Sr 0.125 Fe2O4, Co 0.5 Sr 0.5 Fe2O4, Co 0.625 Sr 0.375 The band gap width of Fe2O4 does not meet the requirements of ideal photocatalytic materials. Therefore, quaternary spinel-type Co2O4 suitable for photocatalysis was selected. 0.125 Sr 0.875 Fe2O4, Co 0.25 Sr 0.75 Fe2O4, Co 0.375 Sr 0.625 Fe2O4.
[0021] The above descriptions are merely a few embodiments of the present invention and are not intended to limit the present invention in any way. Those skilled in the art can readily implement the present invention according to the accompanying drawings and the steps described above. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention, based on the above-described technical content, are equivalent embodiments of the present invention. Furthermore, any equivalent changes, alterations, and variations made to the above embodiments based on the implementation techniques of the present invention are within the protection scope of the present invention.
Claims
1. This invention discloses a screening method for quaternary spinel ferrite photocatalytic materials. A series of quaternary spinel ferrite models are constructed, followed by full structural relaxation using first-principles calculations. The thermodynamic and kinetic stability is evaluated through formation energy and phonon spectrum calculations. Furthermore, the band structure, band edge positions, effective electron mass, and effective hole mass are calculated. The influence of different tetrahedral central atoms on the electronic structure of the spinel material is analyzed and compared. Based on the requirements of ideal photocatalytic materials for electronic structure, effective electron mass, and effective hole mass, suitable quaternary spinel materials for photocatalysis are screened. The implementation of the method includes the following steps: (1) Model building a. Construct a spinel-type Fe3O4 geometric structure model, perform sufficient structural relaxation on it, and obtain the ground-state Fe3O4 geometric structure model; b. Replace all Fe atoms in the tetrahedral center of the ground state Fe3O4 geometric structure model obtained in step (1) a with divalent metal atoms A to obtain the ternary spinel ferrite AFe2O4 geometric structure model. Perform sufficient structural relaxation on it to obtain the ground state AFe2O4 geometric structure model. c. By partially replacing metal atom A in the ground-state AFe2O4 geometric structure model obtained in step (1) b with divalent metal atom B, a quasi-random structure A of quaternary spinel ferrite with different proportions of tetrahedral central elements is constructed. x B y Fe2O4( x + y = 1), and perform sufficient structural relaxation on it to obtain the ground state quaternary A at each scale. x B y Geometric structure model of Fe2O4; (2) Property calculation a. Phonon spectrum calculation The ground-state quaternary spinel A obtained in step (1)c x B y The Fe2O4 geometric structure model was used to perform cell expansion operations, set the corresponding parameters, calculate its phonon spectrum, select the dynamically stable structural model for subsequent calculations, and eliminate unstable models. b. Formation energy calculation Calculate the formation energy of the selected structural model in step (2) a, and select the structural model with a formation energy less than 0 for subsequent calculations; c. Static self-consistent calculation For the structural models selected in step (2)b, perform static self-consistent calculations to generate wave function and charge density data files for each system and obtain ground state energy; d. Calculation of electronic properties Based on the charge density and wave function files obtained in step (2)c, modify the input file parameters and calculate the band structure, band edge position, effective electron mass, and effective hole mass in sequence. (3) Results processing and analysis a. Based on the calculation results of step 2(d), draw the band structure diagram and extract the band gap width; b. Based on the calculation results of step 2(d), draw a diagram showing the relationship between the edge position and the proportion of the tetrahedron's central element; c. Based on the calculation results of step 2(d), calculate the ratio of the effective electron mass to the effective hole mass; d. Based on the results of step (3) ac, analyze and compare the effects of different tetrahedral central atoms on the electronic structure, effective electron mass, and effective hole mass of spinel materials. Based on the requirements of ideal photocatalytic materials for the electronic structure, effective electron mass, and effective hole mass of materials, screen out quaternary spinel materials suitable for photocatalysis.
2. The screening method for quaternary spinel ferrite photocatalytic materials as described in claim 1, characterized in that... The spinel-type Fe3O4 geometric model constructed in step 1(a) is a single cell containing 56 atoms.
3. The screening method for a quaternary spinel ferrite photocatalytic material as described in claim 1, characterized in that... The divalent metal atom A and divalent metal atom B mentioned in step (1)b and step 1(c) are different kinds of divalent metal atoms, namely one of Mg, Ca, Sr, Ba, Zn, Cd, Fe, Co, Ni, Cu and Mn atoms.
4. The screening method for a quaternary spinel ferrite photocatalytic material as described in claim 1, characterized in that... In step (1)c, the mcsqs module of ATAT software is used to obtain the quasi-random structure of the quaternary spinel. Structural relaxation is performed on each generated quasi-random structure, and the structure with the lowest energy is selected as the ground state quaternary A. x B y Geometric structure model of Fe2O4.
5. The screening method for a quaternary spinel ferrite photocatalytic material as described in claim 1, characterized in that... The percentage of the central element A in the quasi-random structure of the quaternary spinel tetrahedron constructed in step (1) ranges from 12.5 at. %, 25 at. %, 37.5 at. %, 50 at. %, 62.5 at. %, 75 at. %, to 87.5 at. %.
6. The screening method for a quaternary spinel ferrite photocatalytic material as described in claim 1, characterized in that... In step (1), the sum of the percentage of the central element A and the percentage of the component B in the quasi-random structure of the quaternary spinel tetrahedron constructed is 1.
7. The screening method for a quaternary spinel ferrite photocatalytic material as described in claim 1, characterized in that... In step (2)a, only the phonon spectrum with no imaginary frequency or an imaginary frequency less than 20 cm⁻¹ is retained. -1 *i's structural model, eliminating phonon spectra with imaginary frequencies greater than 20cm. -1 *i structural model.
8. The screening method for a quaternary spinel ferrite photocatalytic material as described in claim 1, characterized in that... In step (3)d, the screening condition for the effective electron mass and the effective hole mass is that the ratio of the effective hole mass to the effective electron mass is greater than 10.
